RETRACTED: MicroRNA‐320a inhibits invasion and metastasis in osteosarcoma by targeting cytoplasmic polyadenylation element‐binding protein 1 - Yanlong Wang; Jiyu Yang; Pangtao Chen; Yu Song; Weizheng An; Haoran Zhang; Butegeleqi Butegeleqi; Jinglong Yan (Cancer Medicine)
Abstract Osteosarcoma is a primary malignant bone tumor, which affects children, adolescents, and young adults commonly. MicroRNAs (miRNAs) have been proved to be dysregulated in different cancers, including osteosarcoma. Although miR‐320a has been implicated in many types of malignancies, little is known about the role of miR‐320a in osteosarcoma. In this study, we show that the overexpression of miR‐320a or knockdown of cytoplasmic polyadenylation element‐binding protein 1 (CPEB1) inhibited osteosarcoma cell migration and invasion. miR‐320a downregulates CPEB1 expression by directly targeting the CPEB1 3′‐UTR. Furthermore, CPEB1 reintroduction reversed the antiproliferation, antimigration, and antiinvasion roles of miR‐320a, indicating that miR‐320a might function as a tumor suppressor in osteosarcoma through CPEB1. In conclusion, our study demonstrates that miR‐320a plays a critical role in osteosarcoma progression and may provide a potential therapeutic target for osteosarcoma.